Reading while Black : African American biblical interpretation as an exercise in hope - McCaulley, Esau (IVP Academic, an imprint of InterVarsity Press, 2020)
Reading Scripture from the perspective of Black church tradition can help us connect with a rich faith history and address the urgent issues of our times. Demonstrating an ongoing conversation between the collective Black experience and the Bible, New Testament scholar Esau McCaulley shares a personal and scholarly testament to the power and hope of Black biblical interpretation. --